Pattern of Thyroid Illness in a Tertiary Hospital in Nepal - Bhattarai, Arabinda Mohan; Pandeya, Dipendra; Parajuli, Sulochana; Pradhananga, Salina (Medical Journal of Shree Birendra Hospital, 2022)
Introduction: Thyroid dysfunction is an important endocrine disorder worldwide among which hypothyroidism, is attributed to environmental deficiency of iodine. Congenital hypothyroidism is one of the most common preventable causes of intellectual disability worldwide. Hypothyroidism is easily treated and timely detection and treatment of the disorder could reduce the adverse fetal and maternal outcome. The aim of our study is to find the prevalence of thyroid illness in a tertiary health care center of Nepal. Methods: This was a descriptive, cross-sectional study carried out in the Department of Biochemistry of Shree Birendra Hospital, Chhauni, Kathmandu over a period of five months from March 2021 to July 2021. We selected 1000 patients with symptoms suggestive of thyroid disorders. Detailed history was obtained and free triiodothyronine (fT3), thyroxine (fT4) and thyroid stimulating hormone (TSH) estimation was done in Siemens CP Chemiluminescence Immunoassay analyzer. Data were entered in Microsoft Excel and managed in SPSS version 20. Results: Most of our patients with hypothyroidism presented with puffiness of the face, hoarseness of voice, whereas weight loss and restlessness were predominant features in hyperthyroid patients. In our study, the prevalence of hypothyroidism and hyperthyroidism were 16.0% and 9.5% respectively. Conclusions: Hypothyroidism is common in the female population. We found that hypothyroidism and subclinical hypothyroidism were more prevalent in the reproductive age group.